Sir Frank Packer : a biography - Griffen-Foley, Bridget, 1970- (Sydney University Press, 2014)
This absorbing biography traces the newspaper career of Frank's father R.C. Packer from Hobart and the outback to the founding of Smith's Weekly in 1919. Overshadowed by his brilliant father, Frank was an academic failure at school and a mediocre cadet reporter. Despite his own lack of promise as a journalist, Frank came to rule the Australian media landscape with an iron fist.